2003
DOI: 10.1103/physrevlett.91.113002
|View full text |Cite
|
Sign up to set email alerts
|

Rescattering of Ultralow-Energy Electrons for Single Ionization of Ne in the Tunneling Regime

Abstract: Electron emission for single ionization of Ne by 25 fs, 1.0 PW/cm 2 laser pulses at 800 nm has been investigated in a kinematically complete experiment using a "reaction-microscope". Mapping the complete final state momentum space with high resolution a distinct minimum along the longitudinal momentum direction P e|| is observed at P e|| = 0 with respect to the laser polarization direction. Whereas tunneling theory predicts a maximum at the singularity our findings are in good agreement with recent semiclassic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 31 publications
1
61
1
Order By: Relevance
“…One finding deviating from the SFA prediction is the observed low-energy momentum distribution [12,13] of the recoiling ions. Several explanations have been proposed and are still under debate, tracing the effect to the long-range Coulomb potential [14][15][16], Freeman resonances [17,18], or the persistence of ATI peaks in the tunneling regime [19,20].…”
mentioning
confidence: 76%
“…One finding deviating from the SFA prediction is the observed low-energy momentum distribution [12,13] of the recoiling ions. Several explanations have been proposed and are still under debate, tracing the effect to the long-range Coulomb potential [14][15][16], Freeman resonances [17,18], or the persistence of ATI peaks in the tunneling regime [19,20].…”
mentioning
confidence: 76%
“…Due to the capabilities of modern experiments (especially since the advent of cold-target recoil-ion-momentum spectroscopy), both the total yield and the ion-momentum distributions can be measured [12][13][14][15][16][17][18]. It was found that, at high laser intensities, momentum distributions of multiply charged ions along the polarization direction have a Gaussiantype shape with the maximum at zero momentum [14,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…The significance and simplicity within this simple man's model lie in that, after being pumped into the continuum state, the interaction of the electron with the core is much weaker than that with the laser field and, thus, safely can be neglected. However, recent experimental observations have provided strong evidence of the breakdown of the simple man's model, which is based on strong-field approximation (SFA) in both ATI [4][5][6] and HHG [7] processes. These investigations, focused on the low-energy regions of ATI and HHG spectra, have revealed a significant role of the Coulomb interaction of the electron with the ion, which, however, may not be a surprise because, for the slow electrons, their motions can easily be influenced by the Coulomb field [8].…”
mentioning
confidence: 99%
“…Actually, the signature of the Coulomb influence in the high-energy recollision region can be retrieved from the low-energy structure (LES) recently observed in ATI [4,5,9]. The LES is formed due to the transverse momentum concentration of the ATI electrons as evidenced by the energyresolved angular distribution (AD) of the ATI electrons in Fig.…”
mentioning
confidence: 99%